7(u+8)+3u=26

Simple and best practice solution for 7(u+8)+3u=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(u+8)+3u=26 equation:


Simplifying
7(u + 8) + 3u = 26

Reorder the terms:
7(8 + u) + 3u = 26
(8 * 7 + u * 7) + 3u = 26
(56 + 7u) + 3u = 26

Combine like terms: 7u + 3u = 10u
56 + 10u = 26

Solving
56 + 10u = 26

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-56' to each side of the equation.
56 + -56 + 10u = 26 + -56

Combine like terms: 56 + -56 = 0
0 + 10u = 26 + -56
10u = 26 + -56

Combine like terms: 26 + -56 = -30
10u = -30

Divide each side by '10'.
u = -3

Simplifying
u = -3

See similar equations:

| 3x-10+4(x-4)=-12 | | -4y=68 | | 6=y+2 | | 3x-(7a*7a)= | | 16t^2+64+4=S | | |3+-4|-5= | | 17.5=5y | | 5.1=-4u+17.9 | | y^3+16y-y^2-16=0 | | [6-(-8)]-8= | | 7.2=y+(-1.5) | | -(1+0.3r)=-13+7.7r | | 7y=5y(y+2) | | 5x+8-6x+7=112 | | -1.3+(w/2)=-26.9 | | =2cd | | (x+4)(x^2+4x+16)=0 | | -3/7x=3 | | 6(x-1)+4=3x+3(-2+x) | | 9x-23-5x+20=1 | | 16-|-4+6|= | | -3y=-22.5 | | 2a/2 | | 2a+b=115.7 | | 2x^2+(x^2y-2xy^2)= | | 2x/x-2+x/x+3=-5/x+3 | | 5.5=-2+y | | 3/4k+2 | | 150=x+15+3x+1 | | 27x+12=4(6x+2)+3x+4 | | 6a=4a | | -3(pie)+w=2(pie) |

Equations solver categories